A review on recent advancement of electromagnetic interference shielding novel metallic materials and processes. (1st November 2019) - Wanasinghe, Dimuthu; Aslani, Farhad
Abstract: The demand for new materials in the field of electromagnetic interference shielding has increased dramatically in the last few decades due to the advancements in the electronics industry. To meet these growing demands, many new materials are being investigated to replace traditionally used metal sheets. Some of the promising materials being researched are polymer-based composites due to their low specific weight, ease of fabrication, and low cost. Some researchers have also looked into the modification and synthetization of new metal-based shielding materials. One of the significant disadvantages of modifying metallic materials is the reduction of their electrical conductivity that adversely affects the shielding effectiveness. Hence, the modifications carried out should be able to maintain the shielding effectiveness at high values while eliminating the shortcomings of metal sheets. In this review article, novel metal-based materials are analyzed for their shielding effectiveness. While some of the materials reviewed in this paper are merely metal-based composites, others consist of more complex additives including metal oxides and carbides. Apart from the shielding effectiveness, this article analyses the variation of other important properties such as electrical conductivity and mechanical properties for a few of these materials.